Assessing environmental impacts in batik production through life cycle assessment - Asih Hayati Mukti; Juniati; Pratama Risky Putra (BIO Web of Conferences)
This study investigates a small and medium enterprise (SME) in the batik industry located in Pekalongan, Indonesia. The enterprise faces significant challenges due to pollution generated by its production waste, raising serious environmental concerns about air and water quality in the surrounding areas. The research aims to evaluate the environmental impacts of batik production using the Life Cycle Assessment (LCA) method. Findings reveal that the most substantial environmental impact occurs in the Marine Ecotoxicity category. This impact is primarily attributed to the use of chemicals such as sulfuric acid, sodium hydroxide, and sodium carbonate, which dissolve in large quantities of water, leading to marine ecosystem pollution. The study highlights the need for continuous process improvements to achieve more sustainable and environmentally responsible production practices. These improvements align with Sustainable Development Goal (SDG) 12, which focuses on responsible consumption and production.